2019
DOI: 10.4314/gjass.v18i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Proximate, mineral and anti-nutritional compositions of raw and processed African Yambean (<i>Sphenostylis stenocarpa</i>) seeds in Cross River State, Nigeria

Abstract: African yambean (Sphenostylis stenocarpa, Hochst. Ex A. Rich, Harms) is an indigenous legume in tropical Africa. This food crop legume is highly under-exploited and very little scientific information is available in literature. In this study, the chemical composition (proximate, minerals and anti-nutritional profile) of raw and processed African yambean (AYB) seeds was investigated. Seeds of brown seed coat landraces of African yambean were collected from various locations in the Northern part of Cross River S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 27 publications
3
25
5
Order By: Relevance
“…Its seeds and tubers contain 25.6 and 15.9% protein, respectively (Ojuederie and Balogun, 2017; Ojuederie and Balogun, 2019). Similarly, Anya and Ozung (2019) and Sam (2019) reported protein content of 18.55 and 21.61% in seeds. The seeds have in abundance: lysine (6.21–6.60%) and methionine (1.14–1.27%) (Okorie, 2018).…”
Section: Introductionmentioning
confidence: 79%
“…Its seeds and tubers contain 25.6 and 15.9% protein, respectively (Ojuederie and Balogun, 2017; Ojuederie and Balogun, 2019). Similarly, Anya and Ozung (2019) and Sam (2019) reported protein content of 18.55 and 21.61% in seeds. The seeds have in abundance: lysine (6.21–6.60%) and methionine (1.14–1.27%) (Okorie, 2018).…”
Section: Introductionmentioning
confidence: 79%
“…Also, Taofeek et al, 22 opined that anti-nutrients such as tannins, oxalate and trypsin inhibitor are nutritionally disadvantageous when consumed in excess as they form strong insoluble complexes with proteins and divalent metals which result in poor digestion and palatability in humans and animal. [24][25][26] Studies had revealed that excessive consumption of anti-nutrients had an adverse effect on the health status of humans and as well as useful defensive mechanism for plants against herbivours. 23 Also, results revealed that P. lunatus contained a significant amount of most phytochemicals than S. stenocarpa and C. cajan seeds ( Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…African yam bean seed contains protein with a value range between 19 and 30%. The seed is also rich in dietary fibre, carbohydrate, and essential minerals such as calcium, iron, zinc, and magnesium, with values as high as those of other vital legumes [65]. The carbohydrate composition of African yam bean is majorly starch with slowly digestible properties beneficial for diabetic patients [66].…”
Section: African Yam Bean (Sphenostylis Stenocarpa)mentioning
confidence: 99%